The Relationship Between Dysbiosis in Geriatrics and the Risk of HMPV: A Literature Review - Adnexa Miftah Firdausy; Adib Danurdipta; Jodii Arlan Kurnia (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study investigates the relationship between dysbiosis in the geriatric population and the increased risk of Human Metapneumovirus (HMPV) infection through a literature review. The aim of the study is to identify the underlying pathophysiological mechanisms by which dysbiosis affects the immune system, particularly via the gut-lung axis, and its implications for HMPV infection risk. A systematic review was conducted on reputable journals published over the last 10 years (2015–2025) by searching PubMed, Scopus, and ScienceDirect using the keywords "dysbiosis," "geriatrics," "HMPV," "respiratory infection," and "gut-lung axis." The findings indicate that elderly individuals experience a decrease in gut microbiota diversity and an increase in pathogenic bacteria, contributing to a state of inflammaging. This disturbance leads to increased intestinal permeability and the translocation of endotoxins into systemic circulation, which in turn causes excessive immune activation. A reduction in the production of anti-inflammatory short-chain fatty acids (SCFA) was also observed, weakening the immune response to viral infections, including HMPV. The data suggest that the elderly with dysbiosis are at a higher risk of developing serious complications from HMPV, such as pneumonia and exacerbation of pulmonary diseases.The implications of this study support the development of intervention strategies, including the administration of probiotics, prebiotics, and dietary modifications, to restore gut microbiota balance and enhance immune responses in the geriatric population. Although further clinical research is needed to fully elucidate these mechanisms, the findings provide a strong foundation for preventive interventions aimed at reducing the disease burden caused by HMPV.